Persepsi Halal dan Pemahaman Sertifikasi Halal: Studi Deskriptif Analitik - Muhammad Anas; Andre Ridho Saputro; Huliyyatul Wahdah (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2023)
The World Halal Food Council (WHFC) harmonized halal standards and enacted the Job Creation Law with BPJPH, which is in charge of halal registration, certification, and verification, and there is still public understanding that there is no need for halal certification. Research objective: knowing halal perceptions and certification, research method: a descriptive-analytic study. Research results: The survey involved 48 WhatsApp groups with 3,240 members. There were 104 respondents. Four of the 48 WhatsApp groups were business WhatsApp groups, with 225 members. All respondents understood the halal concept, and those who did not understand doubted 21.2%. Of the respondents who understood the term halal certification, 88.5% and 98.1% stated the need for halal labeling. As many as 73.1% of respondents understand that BPJPH and MUI accommodate halal certification, 72.1% of respondents understand that BPJPH manages the administration of halal certification, and 99% of respondents know that halal fatwas are carried out by MUI. Only 30.8% of respondents know that the government facilitates free halal certification. Conclusion: some respondents still do not understand the term syubhat; most are familiar with halal certification, but only a few know about the government's free facilitation of halal certification.